Optimalisasi Kecerdasan Natural Anak di Lingkungan Keluarga - Johar Alimuddin (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2016)
Abstract: The family environment is important in children’s education. Natural intelligence needs to be optimized from an early age so that children are more concerned about the natural environment. Child care for the natural envinaroment preserve nature and can prevent the disaster caused by human activity because of destructive nature. Education in the family environment can optimize the intellegence of natural children in the following ways: pay attention to the child with a loving, giving positive answer to the question posed by children, Giving rules of disipline but not too hard, giving duties related to intelligence naturally, take the kids on vacation to the natural attractions, watch a film about the environment, plants, or animals, reading stories about the environment, plants, or animals. Keywords: Family Education, Natural Intelligence, Child.